Demographic variable and job stress as predictors of depression among primary school teachers in Lagos state of Nigeria (2017)
Issues of increase rate of sick leave, mood swing, fatigue and decreased energy, Feelings of worthlessness and helplessness which could be responsible for discontent and poor morale, low teaching efficiency, poor relationships with pupils, parents and subordinate, premature retirement, more internal conflicts and dysfunctional workplace climate among primary school teachers which can also be link with their wellbeing attracted the attention of this study. This study adopted cross sectional research design and Questionnaires were used to gather data from the primary school teachers. Purposive sampling technique was used to select two hundred primary school teachers who participated in the study. Data collected was analyzed using version 20.0 of statistical package for social sciences. The findings of this study revealed that that there is no significant difference in the depression of female teachers compare to male teachers among primary school teachers in kosofe Local Government Area of Lagos state, Nigeria (t(198)=-1.249, p>.05). it was also discovered that that out of the socio-demographic variable, only monthly income made significant independent contribution to depression among primary school teachers (β=-0.227; t = -2.780; p<0.05). The result also revealed that primary school teachers with high stress reported higher depression than their counterpart with low stress (t(198)=-12.41, p<.05). Further analysis revealed that job stress and working experience had no significant joint influence on depression (F(5,194)=2.975; p>0.05; R=0.171, R2=0.029), and also showed that job stress made significant independent contribution to depression (β=0.162; t = 2.287; p<0.05) while working experience had no significant independent contribution to depression (β=-0.077; t = -1.091; p>0.05). The study concluded that there is significant influence of job stress and monthly income on depression among primary school teachers in kosofe Local Government Area of Lagos state, Nigeria and recommend that government, stakeholders and investors in the field of education should review the job roles of primary school teacher as this study discovered that many of their roles constituted stress and result to depression